2016
DOI: 10.3324/haematol.2015.139899
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib withdrawal syndrome and longer duration of imatinib have a close association with a lower molecular relapse after treatment discontinuation: the KID study

Abstract: T he aim of the Korean Imatinib Discontinuation Study was to identify predictors for safe and successful imatinib discontinuation. A total of 90 patients with a follow-up of ≥12 months were analyzed. After a median follow-up of 26.6 months after imatinib discontinuation, 37 patients lost the major molecular response. The probability of sustained major molecular response at 12 months and 24 months was 62.2% and 58.5%, respectively. All 37 patients who lost major molecular response were retreated with imatinib t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
196
4
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(233 citation statements)
references
References 20 publications
11
196
4
12
Order By: Relevance
“…Secondly, this practice-changing view is reinforced by the demonstration of general improvement of adverse events in both the MMR and MR4 cohorts, with only mild (none > grade 2 severity) and transient evidence of the musculoskeletal symptoms that have recently been described on complete TKI withdrawal 9,15 . Although these and other symptoms generally improved during de-escalation as shown in Figure 3, this trend was not of sufficient strength to be detectable by the quality of life assessment tools used here, emphasising their inappropriateness for well controlled CML patients in the TKI era 16,17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, this practice-changing view is reinforced by the demonstration of general improvement of adverse events in both the MMR and MR4 cohorts, with only mild (none > grade 2 severity) and transient evidence of the musculoskeletal symptoms that have recently been described on complete TKI withdrawal 9,15 . Although these and other symptoms generally improved during de-escalation as shown in Figure 3, this trend was not of sufficient strength to be detectable by the quality of life assessment tools used here, emphasising their inappropriateness for well controlled CML patients in the TKI era 16,17 .…”
Section: Discussionmentioning
confidence: 99%
“…Using this definition of recurrence, at 24 months after TKI cessation the A-STIM and KIDS studies reported that 58-64% of patients are recurrence-free 8,9 and the large EUROSKI study of 868 patients similarly recently reported a rate of 52% at the same time point 10 .…”
Section: Introductionmentioning
confidence: 99%
“…[58][59][60] These findings suggest that immunogenic effects of treatment may affect the probability of TFR success. Other factors associated with successful TFR include achievement of UMRD 9 months after switching from IFN to imatinib, [7] duration of imatinib 62 months, [15] imatinib withdrawal syndrome (i.e. musculoskeletal pain and/or pruritus after stopping imatinib), [15] negative digital PCR at enrollment, [15,16] and age 45 years.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17] In reports of patients who stopped imatinib without achieving deep molecular responses, rapid relapses requiring treatment reinitiation were typical. [56,57] In addition to achievement of deep molecular responses, other potential predictors of TFR success have been assessed in a number of TFR studies (Table 2).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation